Appraisal and ranking of poly-aluminium chloride, ferric chloride and alum for the treatment of dairy soiled water. (1st August 2020) - Mohamed, A.Y.A.; Siggins, A.; Healy, M.G.; Ó hUallacháin, D.; Fenton, O.; Tuohy, P.
Abstract: Land spreading of dairy soiled water (DSW) may result in pollution of ground and surface waters. Treatment of DSW through sludge-supernatant separation using chemical coagulants is a potential option to reduce the negative environmental impacts of DSW. The aims of this study were to (1) assess the effectiveness of three chemical coagulants – poly-aluminium chloride (PACl), ferric chloride (FeCl3 ) and alum – in improving effluent quality, and (2) assess the properties of the sludge that is generated as by-product from the process for its suitability for land application. Taking into consideration optimum doses to minimize pollutants (turbidity, chemical oxygen demand (COD), total phosphorus (TP), total nitrogen (TN), and E. coli ), optimum mixing times and cost, FeCl3 was the best performing coagulant. Generated sludges had higher nutrient content and fewer E. coli than raw DSW, and did not display any evidence of phytotoxicity to the growth of Lolium perenne L. using germination tests. The study discussed the results in a sustainable farm management context, and suggested that the effluent (supernatant) from the treatments may be recycled to wash farm yards, saving water. In parallel, the sludge portion can be applied to amend soil properties with no adverse impacts on the grass growth, providing an agronomic value as an organic fertilizer, and reducing the risk of nutrient losses. This management approach could minimize the overall net cost compared to land application of raw DSW. Highlights: Chemical coagulants showed significant removal of turbidity, COD, TP, TN, and E. coli . Full removal and inactivation of Escherichia coli was achieved by ferric chloride. No evidence of phytotoxicity to the growth of Lolium perenne L. caused by sludges. Effluent from the coagulant treatment could be recycled for yard wash-down. This management approach could minimize the cost compared to land application of DSW.